Peningkatan Implementasi 5S Dan Total Productive Maintenance Dengan Menggunakan Pendekatan Dmaic Dan Expert System (Studi Kasus PT. âXYZâ, Jawa Timur) - Nafida, Wiluddyana Ghoisi; Wardana, ING; Soenoko, Rudy (Rekayasa Mesin, 2012)
This research aimed to increase implementation of 5S (Seiri, Seiton, Seiso, Seiketsu, Shitsuke) and Total Productive Maintenance (TPM) in a paper manufacture company using integration of DMAIC (Define, Measure, Analyze, Improvement, Control) approach and expert system. The DMAIC approach was used for obtain main problem why implementation worked ineffectively, root-cause problem, and improvement solution for business process. Expert system was used to help fastening consultation process while the expert of 5S and TPM, which is few in number, have no time to give consultation. Problems often occurred in 5S and TPM implementation during 2011-2012 are Seiso, Seiton, Autonomous Maintenance, and Seiri. Those problems are caused by the process business that only focused in audit system, instead of 5S implementation stage itself whereas many mechanic or electric still have wrong perception about 5S, and also caused by Autonomous Maintenance that not work effectively. The proposed improvement for the problem are to implement 5S activities on daily activities in simple way in order to introduce 5S culture and increase frequency and control of Autonomous Maintenance. Expert system development delivered application (called SIPAMS) that gives recommendation for main problem. SIPAMS help organization member, such as operator, mechanic, electric and others who didnât receive 5S/TPM implementation training, to consult and to learn basic principles of 5S and TPM.Keywords: 5S, Total Productive Maintenace, DMAIC Approach, Expert System